2006
DOI: 10.1089/met.2006.4.84
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Diet and Exercise on Insulin Resistance during Pregnancy

Abstract: Current evidence suggests that both diet and exercise can alter the usual increase in insulin resistance seen in Western societies during mid and late pregnancy. A low-glycemic diet combined with a low-volume exercise regimen during pregnancy decreases the glucose and insulin response to both mixed caloric intake and exercise, and probably lowers both 24-h blood glucose concentrations and the maternal substrate utilization ratio of carbohydrate/fat. The end result is a marked decrease in both maternal weight g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
6

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 43 publications
(54 reference statements)
1
47
0
6
Order By: Relevance
“…Previous researches have shown insulin resistance was significantly increased in late pregnancy compared with either control or early pregnancy (Kirwan et al, 2002;Melczer et al, 2002). This difference may be related to differences in dietary composition, life style between western and eastern societies (Clapp, 2006;Sivabalan et al, 2008), variability between insulin assays in different experimental researches, differences in the population studied and sampling time during pregnancy (Manley et al, 2008).…”
Section: Discussionmentioning
confidence: 96%
“…Previous researches have shown insulin resistance was significantly increased in late pregnancy compared with either control or early pregnancy (Kirwan et al, 2002;Melczer et al, 2002). This difference may be related to differences in dietary composition, life style between western and eastern societies (Clapp, 2006;Sivabalan et al, 2008), variability between insulin assays in different experimental researches, differences in the population studied and sampling time during pregnancy (Manley et al, 2008).…”
Section: Discussionmentioning
confidence: 96%
“…Kirwan et al (2002);Melczer (2002); Stanley et al (1998) have been shown insulin resistance was significantly increased in late pregnancy compared with either control or early pregnancy. This difference may be related to differences in dietary composition, life style between western and eastern societies (Clapp, 2006), variability between insulin assays in different experimental researches (Manley et al, 2008), differences in the population studied and sampling time during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…The limited evidence from physical activitybased interventions suggests that in order to be more successful in preventing the deterioration of glucose tolerance and insulin sensitivity, pregnant women should engage in regular physical activity at least three times per week at moderate intensity for 30 minutes or more [42][43][44][45][46][47]. However, since glucose response to exercise is influenced by several factors, such as exercise modality, duration, and intensity [48][49][50], further research is needed.…”
Section: Physical Activitymentioning
confidence: 99%